2015
DOI: 10.1038/gene.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

KMT1E-mediated chromatin modifications at the FcγRIIb promoter regulate thymocyte development

Abstract: This work examines the role the lysine methyltransferase KMT1E (Setdb1) in thymocyte development. We have developed and described a T cell-specific conditional knockout of Setdb1. A partial block was seen at the double-positive to single-positive transition, causing reduced numbers of single-positive T cells in the thymus and periphery. Knockout thymocytes had reduced numbers of CD69(+) and T-cell receptor TCRβ(+) cells and increased numbers of apoptotic cells in the double-positive compartment, suggesting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
10
2
Order By: Relevance
“…Different from the ChIP result in the previous report (47), our ChIP-Seq experiment revealed that H3K9me3 profile of the Fcgr2b gene was not altered by ESET deficiency (Supplemental Fig. 3C), indicating that Fcgr2b is not a direct target gene of ESET.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Different from the ChIP result in the previous report (47), our ChIP-Seq experiment revealed that H3K9me3 profile of the Fcgr2b gene was not altered by ESET deficiency (Supplemental Fig. 3C), indicating that Fcgr2b is not a direct target gene of ESET.…”
Section: Discussioncontrasting
confidence: 52%
“…Very recently, the other group reported the effect of ESET (KMT1E) on T cell development by using the same lck-Cremediated T cell-specific ESET-deficient mice (47). They observed similar inhibition of T cell development and aberrant expression of Fcgr2b; however, their conclusion was totally different from ours.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The exact role of each mechanism is, however, still a matter of debate, different studies suggesting a more generalized role for SETDB1 in differentiated cells such as lymphocytes [14,15]. In mice, SETDB1 was shown to ensure Th2 cell stability by repressing ERVs that control the Th1 gene network [15], and also to repress the expression of FcγR-IIb in T cells, an inhibitory Fc receptor regulating the signaling through the TCR complex [16]. Accordingly, SETDB1 knock out induces an increased phosphorylation of ZAP70 in response to CD3 agonism, resulting in an increased cell activation and death at early thymic selection stage.…”
Section: Hervs Are Silenced By Epigenetic Mechanisms At Steady Statementioning
confidence: 99%
“…S5C,D). Interestingly, Fcgr2b is also upregulated in Setdb1-deficient T cells (Martin et al, 2015), although it remains to be determined if derepression of MLV1 can be observed in this context. RT-qPCR analyses for another MLV element (MLV5) similarly revealed strong derepression of the corresponding MLV transcript and upregulation of the neighboring gene (Fig.…”
Section: Setdb1 Mediates MLV Silencing In Pro-b Cellsmentioning
confidence: 99%